Soil-water tension: a feasible criterion for irrigation timing of wheat in the cerrado region - Guerra, Antônio Fernandes; da Silva, Euzébio Medrado; de Azevedo, Juscelino Antônio (Pesquisa Agropecuaria Brasileira, 1994)
The response of wheat (Triticum aestivum L.) to five levels of soil-water tension was studied in a Dark-Red Lotosol of the cerrado region. The crop was irrigated when the soil--water tension reached values of 37, 56, 67, 125 and 536 kPa at a depth of 10 cm. The water was applied by using a plastic hose connected to a PVC perforated tube to assure uniform water distribution on the plots. The grain yield did not show significant differences when soil-water tension values were 37 to 67 kPa, indicating that these levels of tension did not cause detrimental water stress to the plants. The treatments of 125 and 536 kPa resulted in significant differences in grain yield because of a reduction in the number of spikes per m2 and number of grains per spike. The 1,000-grain weight and the hectoliter-grain weight were not affected by the treatments. With the increase in soil-water tension, an almost linear decrease of the total applied water was observed. The applied water to obtain the maximum yield varied from 596 to 796 mm.
Keywords: tensiometers; gypsum blocks; water application